Apprendre à travailler ensemble : influences de l’espace de travail numérique sur l’engagement dans la collaboration - Andrea Tucker; Cédric Fluckiger; Thierry Gidel (Recherches en Éducation)
This article examines the conditions for learners to engage in a joint project as well as the conditions for the development of specific collaboration skills. To better understand engagement in collaboration and the associated skills, we draw on the results of an experiment using multi-touch, multi-user tactile tables. We sought to measure the effects on learner engagement of such a socio-technical training device by comparing three different forms of instrumentation for collaborative activity: a tactile horizontal table and vertical table; a vertical table alone; digital tablets with a vertical table. This allows us to compare how the design of these spaces influences the involvement of individuals in collaboration and the collaborative skills developed.